Activation and Functional Alteration of Mucosal-Associated Invariant T Cells in Adult Patients With Community-Acquired Pneumonia - Ouyang, Lichen; Wu, Mi; Shen, Zhijun; Cheng, Xue; Wang, Wei; Jiang, Lang; Zhao, Juan; Gong, Yeli; Liang, Zhihui; Weng, Xiufang; Yu, Muqing; Wu, Xiongwen (Frontiers in Immunology, 2021)
Community-acquired pneumonia (CAP) remains the significant cause of morbidity and mortality worldwide. Mucosal-associated invariant T cells (MAIT) play key roles in the pathogenesis of children CAP and ICU-associated pneumonia, while their roles in adult CAP is largely unexplored. In this study, we investigated the frequency, phenotype and function of MAIT cells in peripheral blood and bronchoalveolar lavage fluid (BALF) of adult CAP patients. Our data indicate that MAIT cells with elevated levels of CD69 and PD-1 expression are profound declined in peripheral blood of CAP patients. In the BALF, MAIT cells are enriched and express higher levels of CD69 and PD-1 compared to matched blood counterparts. Levels of IL-17A and IFN-γ are increased in BALF of CAP patients. IL-17A/IFN-γ ratio is significantly positively correlated with MAIT frequency in BALF of CAP patients, underling pathogenic role of MAIT-17 cells in CAP. Of note, blood MAIT-cell frequency is strongly negatively correlated with high-sensitivity C-reactive protein (hsCRP) and neutrophil ratio in blood. The ability of circulating MAIT cells to produce IFN-γ is significantly impaired. In summary, our findings suggest the possible involvement of MAIT cells in the immunopathogenesis of adult CAP.